Prehospital teamwork life support service for traffic accident victims - Pereira, Waleska Antunes da Porciúncula; Lima, Maria Alice Dias da Silva (Revista da Escola de Enfermagem da USP, 2009)
The objective of this study is to characterize prehospital teamwork service for traffic accident victims, identifying the actors' activities, the teamwork and the relations with actors from other areas. This is a qualitative study, in which data collection took place by observing the events that occurred at a public service in the city of Porto Alegre, in addition to interviews with each professional involved in the service. The results showed that prehospital care is founded on teamwork and that the understanding among professionals should go beyond the historical hierarchic relation existing in health organizations. There is a need to value the broad field of knowledge, which is associated with the core of care activities that meet most trauma victim needs.